Propuesta de estudio red de telemedicina de Bogotá - Angulo Chavarro, Jaime Humberto; Aparicio Pico, Lilia Edith; Benitez Forero, Jaime Antonio; González Rodríguez, Ivan Fernando (Ingeniería, 1999)
In this paper, is presented a project for the study of the hospital medical services and the local telecommunication carriers services to stablish a model of the telecommunication network: supported by carriers to carry on the matrixes of the hospital medical services and the telecommunication operators. The line group for investigation in Telemedicine at the Distrital University Francisco José de Caldas, are looking for parameters well stablish to mounth the proof pilot: getting this way, amplify the specialist coverage to the areas where not favored inhabitants live in the capital, improving the healt care services.